2003
DOI: 10.1017/s1074070800005897
|View full text |Cite
|
Sign up to set email alerts
|

Economic Hysteresis in Variety Selection

Abstract: Investing in a new perennial crop variety involves an irreversible commitment of capital and generates an uncertain return stream. As a result, the decision to adopt a new variety includes a significant real option value. Waiting for returns to rise above this real option causes a delay in adoption because of economic hysteresis. This study tests for hysteresis in the adoption of wine grape varieties using a sample of district-level data from the state of California. The empirical results show a significant hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…However, farmers' adaptations to a dynamic environment are often characterised by some kind of inertia in which farmers respond surprisingly slow to changes. Examples of such inertia have been reported in (dis)adoption studies that focused on a range of agricultural technologies, such as irrigation technology (Carey and Zilberman 2002;Seo et al 2008), conservation intervention (Winter-Nelson and Amegbeto 1998), investment in new perennial crop varieties (Richards and Green 2003) and land conversion (Frey et al 2013). Several reasons have been offered to explain farmers' slow response, including economic and sociological factors, such as financial constraints (Huettel et al 2010), risk aversion (Knight et al 2003) and nonmonetary goals of the decision-maker (Musshoff and Hirschauer 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, farmers' adaptations to a dynamic environment are often characterised by some kind of inertia in which farmers respond surprisingly slow to changes. Examples of such inertia have been reported in (dis)adoption studies that focused on a range of agricultural technologies, such as irrigation technology (Carey and Zilberman 2002;Seo et al 2008), conservation intervention (Winter-Nelson and Amegbeto 1998), investment in new perennial crop varieties (Richards and Green 2003) and land conversion (Frey et al 2013). Several reasons have been offered to explain farmers' slow response, including economic and sociological factors, such as financial constraints (Huettel et al 2010), risk aversion (Knight et al 2003) and nonmonetary goals of the decision-maker (Musshoff and Hirschauer 2008).…”
Section: Introductionmentioning
confidence: 99%
“…McDonald and Siegel, 1986;Dixit and Pindyck, 1994;Trigeorgis, 1996). Recently, the approach has been applied, among other things, to the adoption of soil conservation measures (Winter-Nelson and Amegbetto, 1998), marketing (Richards and Green, 2003), wilderness preservation (Conrad, 2000), agricultural labour migration (Richards and Patterson, 1998), the introduction of herbicide-tolerant sugar beets in the EU ) and the analysis of government reforms (Leitzel and Weisman, 1999). In the case of transgenic crops there are the additional irreversible government policy costs of the implementation of biosafety regulations and changes in patent laws.…”
Section: Introductionmentioning
confidence: 99%
“…These flexibility values can be substantial, so NPVs based on current land use cannot truly reflect the opportunity cost of land where alternative land uses are available. It is likely that farmers have at least an intuitive understanding of the trade-off between current returns and future flexibility, which may in part explain why major land use decisions are often made more slowly than simple cost-benefit models suggest (Carey and Zilberman, 2002;Richards and Green, 2003;Odening et al, 2005). Economic experiments have also found that farmers tend to make irreversible investments later than NPV models predict, though sooner than optimal under real options values; with experience, farmer decisions come to more closely approximate the real options framework .…”
Section: Discussionmentioning
confidence: 99%
“…Odening et al, 2005;Stokes et al, 2008;Tozer, 2009;Tozer and Stokes, 2009;Musshoff, 2012). This may account for the low levels of uptake of new practices which have been observed among farmers, even when such practices are profitable at current price levels (Carey and Zilberman, 2002;Richards and Green, 2003;Odening et al, 2005). Di Corato et al (2013) demonstrate the uncertainty around the future opportunity cost (in terms of foregone agricultural production) can delay the adoption of forestry for bio-energy, unless subsidies are provided.…”
Section: Introductionmentioning
confidence: 99%